A distance-based probabilistic routing for underwater acoustic sensor networks. (1st January 2013) - Zhang, Song; Li, Deshi
Underwater Acoustic Sensor Networks (UASNs) have received significant attention recently. The important characteristic of an underwater acoustic sensor network is that, most underwater acoustic sensor nodes have a certain beam width and a three-dimensional direction, which are ignored by the existing underwater routing protocols. This characteristic will lead to the sharp decline of the existing protocol performance. We develop a Distance-Based Probabilistic Routing (DBPR) protocol to tackle this problem in UASNs. DBPR uses forward probability to determine whether to forward the data packet. Forwarding probability is influenced by the distance and the beam width of the node. A key advantage of our protocol is that it can achieve relatively high packet delivery rate and ensure reasonable energy consumption when taken into account the above characteristic. The proposed protocol is compared with a representative routing protocol for UASNs. The simulation results verify the effectiveness and feasibility of the proposed work.